THE EFFECT OF SELF-EFFICACY AND COMMUNITY ENGAGEMENT ON THE PERFORMANCE OF CULINARY MSMEs IN SURAKARTA - Bakar Akbar, Abu; Lubis, Arowadi; Rizki R, Muhammad (ITB AAS Indonesia Surakarta, 2025)
This study aims to identify the concepts of Self Efficacy and Community Engagement. From the two concepts, it is analyzed which one has the dominant influence on the performance of culinary MSMEs. With a quantitative approach from samples taken in Pasar Kikwon and Serengan sub-districts, it is expected to be able to contribute to the MSME development map in Surakarta. The research results show that: The effect of self efficacy partially influence increasing of sales. Community engagement on the performance of culinary MSME has been implemented well and has been realized with increasing volume of sales. From the description, it can be concluded that in the implementation of business ethics in trading drinks at Teh Tarik Jodi Manahan, thus, the conclusion of the description is that despite facing obstacles in the implementation of Islamic business ethics, Teh Tarik Jodi Manahan has succeeded in overcoming these challenges by finding creative solutions and in accordance with the principles of Islamic business. This reflects their commitment to continue running their business in accordance with the principles of Islamic business ethics.